2019
DOI: 10.1001/jamaoncol.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Collaborative Telerehabilitation on Functional Impairment and Pain Among Patients With Advanced-Stage Cancer

Abstract: IMPORTANCE Most patients with advanced-stage cancer develop impairment and pain-driven functional losses that jeopardize their independence. OBJECTIVE To determine whether collaborative telerehabilitation and pharmacological pain management improve function, lessen pain, and reduce requirements for inpatient care. DESIGN, SETTING, AND PATIENTS The Collaborative Care to Preserve Performance in Cancer (COPE) study was a 3-arm randomized clinical trial conducted at 3 academic medical centers within 1 health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 117 publications
(150 citation statements)
references
References 50 publications
2
136
0
Order By: Relevance
“…A randomized trial that compared high‐intensity and low‐intensity exercise programs found that the former were cost‐effective, mostly due to significantly lower health care costs in the high‐intensity exercise group . Several studies noted reductions in unplanned hospitalizations, lengths of stay, and emergency room visits among patients who participated in exercise programming . Although it is often assumed that multidimensional programs offer larger benefits, they are also inherently more expensive.…”
Section: Implementation Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized trial that compared high‐intensity and low‐intensity exercise programs found that the former were cost‐effective, mostly due to significantly lower health care costs in the high‐intensity exercise group . Several studies noted reductions in unplanned hospitalizations, lengths of stay, and emergency room visits among patients who participated in exercise programming . Although it is often assumed that multidimensional programs offer larger benefits, they are also inherently more expensive.…”
Section: Implementation Issuesmentioning
confidence: 99%
“…87 Several studies noted reductions in unplanned hospitalizations, lengths of stay, and emergency room visits among patients who participated in exercise programming. 88,89 Although it is often assumed that multidimensional programs offer larger benefits, they are also inherently more expensive. It is as yet unclear whether such programs are more cost-effective compared with monodimensional programs.…”
Section: Cost and Compensationmentioning
confidence: 99%
“…There are a few examples in which the use of technology can support virtual cancer exercise and cancer rehabilitation systems, but they need further testing for feasibility, usability, acceptability, and implementation for a variety of populations . Telehealth care is one type of delivery that needs further testing but recently was found to improve function, decrease pain, and decrease health care service use, aiding community clinicians and increasing the reach of cancer rehabilitation in rural and/or low‐resource settings . The use of technology also can revolutionize the evaluation of value metric reporting, and by adding real‐time assessment of outcomes and quality.…”
Section: Introductionmentioning
confidence: 99%
“…The randomized clinical COPE trial assigned 516 patients who were experiencing functional limitations to: (a) a control group (arm A), (b) tele‐rehabilitation (arm B), and (c) tele‐rehabilitation plus pharmacological pain management (arm C). Clinical outcomes of this trial have been reported elsewhere . All arms underwent automated home‐based monitoring of physical functioning and pain via telephone and/or internet, with reporting of these data to their care teams.…”
Section: Methodsmentioning
confidence: 99%
“…These assumptions have been challenged by reports of reduced hospital and emergency department service utilization among patients randomized to quality of life‐ and symptom‐directed interventions that improve pain and/or function . The recently reported Collaborative Care to Preserve Performance in Cancer (COPE) was notable among these efforts as the first to significantly reduce hospital lengths of stay and requirements for post‐acute care by targeting pain and function . Moreover, the COPE trial enrolled patients with advanced stage cancers, a population whose hospitalizations account for up to two‐thirds of their health‐care costs.…”
Section: Introductionmentioning
confidence: 96%